2019
DOI: 10.1101/533414
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Length of uninterrupted CAG repeats, independent of polyglutamine size, results in increased somatic instability and hastened age of onset in Huntington disease

Abstract: Huntington disease (HD) is an autosomal dominant neurological disorder that is caused by a CAG repeat expansion, translated into polyglutamine, in the huntingtin (HTT) gene. Although the length of this repeat polymorphism is inversely correlated with age of onset (AOO), it does not fully explain the variability in AOO. Genomic studies have provided evidence for the involvement of DNA repair in modifying this trait, potentially through somatic repeat instability. We therefore assessed genetic variants within th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In Drosophila, CAG tracts interspersed with the degenerate codon, CAA is associated with less severe phenotype 11 . The same effect was also seen in human patients 12,13 with a recent report showing up to 25 year reduction in age of onset due to the loss of CAA interruptions in HD patients 14 . This is important as CAG repeat toxicity is often linked to its hairpin structure seen in vitro, which is disrupted when it is interspersed with CAA 15 .…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…In Drosophila, CAG tracts interspersed with the degenerate codon, CAA is associated with less severe phenotype 11 . The same effect was also seen in human patients 12,13 with a recent report showing up to 25 year reduction in age of onset due to the loss of CAA interruptions in HD patients 14 . This is important as CAG repeat toxicity is often linked to its hairpin structure seen in vitro, which is disrupted when it is interspersed with CAA 15 .…”
Section: Introductionsupporting
confidence: 69%
“…This suggests that a deeper understanding of common factors that trigger interferon signaling in neurodegeneration are needed. Several lines of evidence indicate that CAG repeats, a common feature of these diseases, may manifest their neuronal toxicity through RNA 14,16,18,20,34 . Although the spinocerebellar ataxias are largely caused by CAG repeat expansions in coding regions, several diseases like SCA12 have CAG repeat expansions in untranslated regions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genome-wide association studies (GWASs) for modifiers of HD age of onset provide compelling evidence that uninterrupted CAG repeat length, instead of polyQ repeat length, is more closely associated with motor disease onset in HD (GeM-HD, 2019; Wright et al, 2019). By examining the presence, absence, or duplication of the terminal CAA-CAG sequences (both encoding glutamine residues) in HTT, it was found that HD onset is best predicted by uninterrupted CAG repeat length and less well predicted by the polyQ repeat length (GeM-HD, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A few individuals have no CAA interruption or 2 CAAs instead of 1. The number of such interruptions was found by 2 independent groups to influence the age of HD onset and progression, even though they lie between the genetic test ' s markers and encode glutamine residues, so the result of the HD genetic test in such individuals is still a correct reflection of the length of the polyglutamine tract. There is clearly something happening at the DNA level that gives these CAA interruptions an unexpected and surprisingly robust influence.…”
Section: Overturning Fundamental Assumptionsmentioning
confidence: 99%